Stem Cell-Derived Exosome as Potential Therapeutics for Microbial Diseases - Keshtkar, Somayeh; Kaviani, Maryam; Soleimanian, Saeede; Azarpira, Negar; Asvar, Zahra; Pakbaz, Sara (Frontiers in Microbiology, 2022)
Exosomes, as the smallest extracellular vesicles that carry a cargo of nucleic acids, lipids, and proteins and mediate intercellular communication, have attracted much attention in diagnosis and treatment in the field of medicine. The contents of exosomes vary depending on the cell type and physiological conditions. Among exosomes derived from several cell types, stem cell-derived exosomes (stem cell-Exo) are increasingly being explored due to their immunomodulatory properties, regenerative capacity, anti-inflammatory and anti-microbial functions. Administration of stem cell-Exo, as a cell-free therapy for various diseases, has gained great promise. Indeed, the advantages of exosomes secreted from stem cells outweigh those of their parent cells owing to their small size, high stability, less immunogenicity, no risk of tumorigenesis, and easier condition for storage. Recently, the use of stem cell-Exo has been proposed in the field of microbial diseases. Pathogens including bacteria, viruses, fungi, and parasites can cause various diseases in humans with acute and chronic complications, sometimes resulting in mortality. On the other hand, treatments based on antibiotics and other chemical compounds have many side effects and the strains become resistant to drugs in some cases. Hence, this review aimed to highlight the effect of stem cell-derived extracellular vesicles including stem cell-Exo on microbial diseases. Although most published studies are preclinical, the avenue of clinical application of stem cell-Exo is under way to reach clinical applications. The challenges ahead of this cell-free treatment that might be applied as a therapeutic alternative to stem cells for translation from bench to bed were emphasized, as well.